ANALISIS PENGARUH PERATURAN MENTERI KEUANGAN NOMOR 102/PMK.011/2011 DAN NOMOR 90/PMK.011/2011 TERHADAP KEGIATAN PERFILMAN DI INDONESIA - ARDI, SELVIA (Jurnal Akuntansi AKUNESA, 2013)
Taxation issues that occur between the importer's film and the governmentabout royalty tax rate and the amount of import duties.The effect of application ofPMK No.102/PMK.011/2011 and PMK No.90/PMK.011/2011 for import filmbusiness. The purpose of this study to describe the impact of the implementation ofthe PMK. Increase in the amount of taxes to be paid by importers of an impact onincreasing the cost of the film and also an increase in cinema ticket rates.Keywords: Importer film, Film imports, Tax rate, PMK No.102/PMK.011/2011and PMK No.90/PMK.011/2011